Identifying Factors for Creating Healing Environments - Ghassem Mottalebi; Ladan Vojdanzadeh (صفه)
In line with the evolution of human needs, the impact of environment on human health and safety has gained more significance. This is particularly important in case of medical spaces, where the patient is subject to serious stress caused by illness, medication, restrictions, feeling of isolation and concerns for medical expenses. The hospital environment can aggravate the situation with poor interior design. This requires that medical spaces create an atmosphere of joy, friendliness, delight and trust. As such, a ‘healing environment’ can be described as an environment created to assist the recovery process. By definition, ‘healing’ concerns psychological and spiritual aspects of recovery, in contrast with ‘curing’ which is a primarily physical concept. This research demonstrates that changes in certain design properties of healthcare facilities can reduce stress and in consequence, its adverse impacts on the recovery process. This can also help increase staff confidence and efficiency leading to a reduction in prescription errors and unwanted spread of infections. Such changes include increased day lighting, adequate ventilation, reduction of noise, and access to natural features such as vistas looking towards sky and vegetation. The increased ‘affordance’ of the healing environment can thus alleviate stress and help the recovery process.